Leveling the Field for Renewables : Mexico's New Policy Framework for Incorporating External Costs of Electricity Generation - World Bank (Washington, DC, 2014)
Mexico has started a number of efforts to develop adequate policy frameworks in several areas including the energy sector, transportation and industrial policies, and forestry and natural resources management. Its Climate Change Law and the National Strategy on Climate Change envision is changing the upward trend of its carbon dioxide emissions towards a total decline of emission of thirty percent by 2020, and fifty percent by 2050. Achieving these ambitious policy goals is challenging for the country and will require many distinct efforts to mainstream climate change in policy design. Careful economic analysis will be critical to effectively reduce emissions while allowing for sustainable development. The policy evaluated in the study is part of Mexico's policy framework to promote renewable energy. The Ministry of Energy in Mexico, SENER, has issued a Methodology to incorporate external costs of electricity generation. While external costs are not privative of fossil energy, the Mexican government has started this process by focusing on the external costs on health and climate change, two of the main impacts of energy use. The study analyzes the potential of this new policy to help Mexico in its energy and environmental goals. It is organized into five chapters: (i) Introduction; (ii) Mexico s Policy Context for Incorporating Externalities; (iii) Valuation of Externalities; (iv) Internalizing Externalities; and (v) Conclusion. Included are four annexes: Method to Value Externalities for Mexico's Electricity Generation; Investment Plan in the Power Sector in Mexico; Modeling Framework and Methodology; and Project Valuation with Environmental Externalities.